Student’s Perception On The Use Flipped Classroom In Learning English at The Second Grade Of SMPN 2 X Koto - Ira Yani Eka Putri; Genta Sakti; Syahrul Syahrul; Irwandi Irwandi (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aimed to investigate the students’ perceptions of the flipped classroom approach in learning English at SMPN 2 X Koto Tanah Datar. The flipped classroom model, which reversed traditional in-class activities and homework, introduced new content at home through videos or readings, and dedicated class time to interactive, hands-on activities. This method sought to enhance student engagement, promote active learning, and provide opportunities for personalized instruction and immediate feedback. The study employed a descriptive quantitative method, focusing on second-grade students. Data were collected using a questionnaire that was distributed to 64 students, who were selected through purposive sampling. The questionnaire aimed to gauge students' perceptions of various aspects of the flipped classroom, including self-directed learning, collaboration, responsibility, learning performance, flexibility, and student satisfaction. The population for this study consisted of all second-grade students at SMPN 2 X Koto for the academic year 2021/2022, totaling 95 students across three classes. The sample was selected using purposive sampling, focusing on classes VIII.1 and VIII.2, to ensure participants had the specific attributes necessary for the research. Based on the findings and analysis, it can be concluded that students at SMPN 2 X Koto Tanah Datar have a highly favorable perception of the Flipped Classroom approach in learning English. The study, which involved 95 second-grade students, revealed positive responses across various aspects such as autonomy in learning, collaboration, responsibility, learning performance, flexibility, individualized experiences, interactions, and overall satisfaction. With an average score of 81.41%, categorized as "Very Good" by Arikunto's criteria, the Flipped Classroom methodology is well-received and deemed beneficial for English education at SMPN 2 X Koto Tanah Datar.